Catalytic oxidative desulphurization of pyrolytic oils to fuels over different waste derived carbon-based catalysts. (15th July 2021) - Tamborrino, Valentina; Costamagna, Giulia; Bartoli, Mattia; Rovere, Massimo; Jagdale, Pravin; Lavagna, Luca; Ginepro, Marco; Tagliaferro, Alberto
Graphical abstract: Highlights: Carbothermal synthesis of iron nanoparticle anchored onto waste derived carbon. Catalytic oxidative desulphurization of tires oil with [S] of 7139 ppm was studied. Effects of temperature, time, catalyst loading and supports were evaluated. A desulphurization of up to of 60% was reached. Abstract: In this work, we reported the conversion though carbothermal process of two catalysts produced by pyrolyzing exhausted coffee and waste tires. We tailored the surface with anchored iron nanoparticles through a facile carbothermal route and tested them for catalytic oxidative desulphurization of high sulphur content oil derived from tires pyrolysis. We studied their activity in a biphasic system under different conditions reaching a desulphurization of up to of 60% by using an oil with a sulphur concentration of up to 7139 ppm. The extensive characterization proved the reliability of those materials as promising catalysts for upgrading of sulphur rich drop-in fuels.